Climate change and nutrition - Thomson, Madeleine; Fanzo, Jessica (International Food Policy Research Institute, 2015)
Given the widespread effects that climate change is projected to have on the world’s most vulnerable people—and indeed the effects that are already underway—climate change features strongly in the Sustainable Development Goals (SDGs): specifically, SDG 13 calls for “urgent action to combat climate change and its impacts.” Among the many concerns related to climate change, its potentially serious implications for agriculture and food security have long been recognized.